PENERAPAKAN PENDEKATAN REALISTIC MATHEMATIC EDUCATION (RME) PADA SISWA KELAS IV SDUNTUK MENGUKUR BERPIKIR KRITIS - Amirotul Fauziah; Neni Mariana (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2025)
The purpose of this study is to measure with the Realistic Mathematics Education (RME) approach that focuses on improving critical thinking of 4th grade students on the material of fractions of one numerator. 10 4th grade students of SDN Gading Krembung Sidoarjo as research subjects. Classroom action research with the method of Kemmis Mc Taggart. Observation sheets, worksheets, test questions are used as research instruments to measure critical thinking. Qualitative and comparative descriptive analysis techniques. The results of the increase were seen from the results of the initial observation of meeting 1 and meeting 2 of 50% and 65%, so that there was an increase in succession, namely meeting 1 and meeting 2 in the first stage of 83.5% and 87% in the first stage increased to 88.5% and 95% in the second stage in the sense that the RME approach can show that it is efficient and effective in improving critical thinking of grade 4 students on the material of fractions of one numerator. The limitation of this research is that the range of research is still small, it is hoped that further researchers can compare with at least 2 elementary schools and fraction material is not only one numerator but can be with equal numerators and others.